The Integration and Securitization of Muslim Migrants in Europe - Nawwar, Yasmeen (AUC Knowledge Fountain, 2021)
In its efforts to integrate newly entering migrants into their societies, Europe has established integration policies that negatively impact these migrants, especially those from racialized backgrounds. The policies mask an agenda of securitization against outsiders who are falsely considered to be a danger to national security and national identity. Since the 9/11 attacks on the World Trade Center in the United States, many Western countries, including European countries, began to build a culture of fear against Muslims. Europe began to increasingly associate migrants with problems such as trafficking, radicalization, and terrorism. As a result, Europe began to treat migration as a security issue and migrants as the targets of the security policies. Governments established integration policies and citizenship laws so difficult that migrants began to find it harder to integrate, contributing to a genuine feeling of exclusion from society. Additionally, security forces were given the responsibility of vetting migrants and determining who could enter European states and who could not. Slowly, Muslim migrants came to be associated with criminality and danger. European governments allowed security forces to monitor Muslim migrants, fearing their radicalization, and allowed raids to take place against Muslims’ homes and cultural spaces. Furthermore, European countries established legislations banning religious symbols, a move done to hide the true intention of banning the Muslim veil, making it difficult for Muslim women from practicing a normal life while wearing the veil. While theoretically they seem to be advocating for migrants and their inclusion, in practice, through their security-infused integration policies, Europe has targeted Muslim migrants in a new security regime, specifically tailored for migration.